Influence of single-nucleotide polymorphisms in TLR3 (rs3775291) and TLR9 (rs352139) on the risk of CMV infection in kidney transplant recipients - Redondo, Natalia; Rodríguez-Goncer, Isabel; Parra, Patricia; Ruiz-Merlo, Tamara; López-Medrano, Francisco; González, Esther; Polanco, Natalia; Trujillo, Hernando; Hernández, Ana; San Juan, Rafael; Andrés, Amado; Aguado, José María; et al. (Frontiers in Immunology, 2022)
Risk stratification for cytomegalovirus (CMV) infection after kidney transplantation (KT) remains to be determined. Since endosomal toll-like receptors (TLRs) are involved in viral sensing, we investigated the impact of common single-nucleotide polymorphisms (SNPs) located within TLR3 and TLR9 genes on the occurrence of overall and high-level (≥1,000 IU/ml) CMV infection in a cohort of 197 KT recipients. Homozygous carriers of the minor allele of TLR3 (rs3775291) had higher infection-free survival compared with reference allele carriers (60.0% for TT versus 42.3% for CC/CT genotypes; P-value = 0.050). Decreased infection-free survival was observed with the minor allele of TLR9 (rs352139) (38.2% for TC/CC versus 59.3% for TT genotypes; P-value = 0.004). After multivariable adjustment, the recessive protective effect of the TLR3 (rs3775291) TT genotype was confirmed (adjusted hazard ratio [aHR]: 0.327; 95% CI: 0.167–0.642; P-value = 0.001), as was the dominant risk-conferring effect of TLR9 (rs352139) TC/CC genotypes (aHR: 1.865; 95% CI: 1.170–2.972; P-value = 0.009). Carriers of the TLR9 (rs352139) TC/CC genotypes showed lower CMV-specific interferon-γ-producing CD4+ T-cell counts measured by intracellular cytokine staining compared with the TT genotype (median of 0.2 versus 0.7 cells/μl; P-value = 0.003). In conclusion, TLR3/TLR9 genotyping may inform CMV infection risk after KT.